Case Report: Two different acromelic dysplasia phenotypes in a Chinese family caused by a missense mutation in FBN1 and a literature review - Tian, Fengyan; Dong, Xiao; Yuan, Ruyue; Hou, Xiaohan; Qing, Jing; Li, Yani (Frontiers in Pediatrics, 2024)
Background: Acromelic dysplasia caused by FBN1 mutation includes acromicric dysplasia (AD), geleophysic dysplasia 2 (GD2), and Weill-Marchesani syndrome 2 (WMS2). All three diseases share severe short stature and brachydactyly. Besides phenotypic similarity, there is a molecular genetic overlap among them, as identical FBN1 gene mutations have been identified in patients with AD, GD2, and WMS2. However, no family with different acromelic dysplasia phenotypes due to the same variant has been described in English reports. Case report: The proband presented with typical facial features, severe short stature, short limbs, stubby hands and feet and radiological abnormalities. Her elder sister and mother had similar physical features. In addition, her elder sister was found to have aortic valve stenosis by echocardiography. Mutation analysis demonstrated a heterozygous missense mutation, c.5179C>T (p.Arg1727Trp) in exon 42 of the FBN1. The proband and her mother were diagnosed with AD, and her elder sister with GD2. The proband was treated with recombinant human growth hormone (rhGH) and had a body length gain of 0.72 SDS in half a year. Conclusion: These findings expand the phenotypic spectrum of FBN1 gene mutations and highlight that identical FBN1 genotypes can result in different phenotypes of acromelic dysplasia in a family. The efficacy of rhGH therapy in patients with acromelic dysplasia is controversial. More follow-up is needed on the long-term efficacy of rhGH therapy.